2018
DOI: 10.17533/udea.iee.v36n1e08
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Nursing Care: Perception of Parents of Newborns Hospitalized in Neonatal Units

Abstract: Parents perceive as positive the nursing care their children receive in the neonatal unit. However, in the analysis by dimensions, it is possible to establish the need to strengthen aspects, like interpersonal relations and communication processes, which are part of the dimensions: Explains and facilitates and Anticipates. The findings permit guiding specific actions to improve quality in neonatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Nowadays, the maintenance and improvement of the quality of nursing care is the most important challenge for nursing care systems around the world [ 4 ]. The first step in improving the quality of nursing care is to evaluate and analyze the quality of provided care and examine the factors affecting on it [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the maintenance and improvement of the quality of nursing care is the most important challenge for nursing care systems around the world [ 4 ]. The first step in improving the quality of nursing care is to evaluate and analyze the quality of provided care and examine the factors affecting on it [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies covered the care between birth and discharge or birth to 72 hours,14 18–20 23 26 27 30 33–35 41 43 46 49 51–58 61 62 64 67 69–73 76 78–80 82–85 four studies reported on follow-up care at home,16 47 48 50 one on care during ground ambulance transport37 and five studies covered end-of-life care 25 36 42 72 84. We found no studies that reported on home birth.…”
Section: Resultsmentioning
confidence: 89%
“…From the included studies, almost half (35/72) studied parents or carers’ experience with newborn care,17–51 although only 19 had this as a primary aim. Of those 19, eight focused on overall parental experience with newborn care,22 27 30 32 38 42 43 45 the remaining eleven focused on specific aspects of care, such as kangaroo mother care (KMC) provision,37 41 discharge education,26 postnatal diagnoses,18 24 end of life care21 25 31 or home-based postnatal care 47 48 50.…”
Section: Resultsmentioning
confidence: 99%
“…These actions, carried out in a hospital setting, provided satisfaction and safety to caregivers, which corroborates the re-sults of a study carried out at the University Hospital of Minas Gerais, Brazil, in which parents of newborns reported feeling motivated to care, support which they received from the nursing team during hospitalization (8) . A study carried out in Colombia also evidenced the positive performance of the nursing team involving the family members in the care process to the newborn, which favored integral, humanized and safe care (9) . Awareness of the actual health condition of the newborn and the early involvement of caregivers in care can strengthen the bond.…”
Section: Discussionmentioning
confidence: 99%